The role of instrumental emotion regulation in the emotions-creativity link: How worries render neurotic individuals more creative - LEUNG, Angela K.-Y. (Institutional Knowledge at Singapore Management University, 2013)
Based on the instrumental account of emotion regulation, the current research seeks to offer a novel perspective to the emotions-creativity debate by investigating the instrumental value of trait-consistent emotions in creativity. We hypothesize that emotions such as worry (vs. happy) are some trait-consistent experiences for neurotic individuals and experiencing these emotions can facilitate performance in a creativity task. In two studies, we found support for our hypothesis. First, individuals higher in neuroticism had a greater preference for recalling worrisome (vs. happy) events in anticipation of performing a creativity task (Study 1). Moreover, when induced to recall a worrisome (vs. happy) event, individuals higher in neuroticism had better performance in a creativity task (Study 2). These findings offer a new perspective to the controversy concerning the emotions-creativity relationship and further demonstrate the role of instrumental emotion regulation in the domain of creative performance.